2010
DOI: 10.1590/s0074-02762010000300003
|View full text |Cite
|
Sign up to set email alerts
|

Culex quinquefasciatus vitellogenesis: morphological and biochemical aspects

Abstract: The vitellogenic process in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 46 publications
0
17
0
3
Order By: Relevance
“…However, this simple cell composition does not imply decreased organ metabolism complexity and multitasking ability. For instance, it plays a role in the storage and metabolism of energetic molecules, detoxification, egg yolk precursor synthesis, magnetoreception and immune response (Bian et al 2005, Feitosa et al 2006, Roy et al 2007, Antonova et al 2009, Cardoso et al 2010, Roy & Raikhel 2011. The fat body also actively participates in insect homeostasis by regulating the concentration of substances in the haemolymph (for review see Haunerland & Shirk 1995, Arrese & Soulages 2010 and it has also been suggested that it represents a model for a better understanding of metabolism and physiology following cell aging (Hsieh & Hsu 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this simple cell composition does not imply decreased organ metabolism complexity and multitasking ability. For instance, it plays a role in the storage and metabolism of energetic molecules, detoxification, egg yolk precursor synthesis, magnetoreception and immune response (Bian et al 2005, Feitosa et al 2006, Roy et al 2007, Antonova et al 2009, Cardoso et al 2010, Roy & Raikhel 2011. The fat body also actively participates in insect homeostasis by regulating the concentration of substances in the haemolymph (for review see Haunerland & Shirk 1995, Arrese & Soulages 2010 and it has also been suggested that it represents a model for a better understanding of metabolism and physiology following cell aging (Hsieh & Hsu 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Trophocyte inclusions represent fat, protein and sugar reserves used by insects to meet their energy demands during reproduction and diapause, to provide energy for the developing embryo and to provide energy for prolonged periods of flight (Arrese & Soulages 2010). Trophocytes are highly specialised for protein synthesis (Raikhel & Lea 1983, Snigirevskaya et al 1997, Cardoso et al 2010) and large amounts of vitellogenic proteins have to be synthesised during mosquito vitellogenesis. Notably, the trophocytes from newly emerged An.…”
Section: Discussionmentioning
confidence: 99%
“…As vitelogeninas são fosfolipoproteínas glicosiladas oligoméricas, com massa molecular variando entre 200 e 600 kDa, são clivadas proteoliticamente em duas ou mais subunidades (Clements, 1992) (Cardoso et al, 2010). A vitelogenina chega ao ovário pela hemolinfa e é internalizada por intermédio de receptores, encontrados nas membranas celulares dos ovócitos.…”
Section: O Mosquitounclassified
“…Em Cx. quinquefasciatus, o ovócito e as sete células auxiliadoras não podem ser diferenciados por microscopia antes do repasto sanguíneo (Cardoso et al, 2010).…”
Section: O Mosquitounclassified
See 1 more Smart Citation